Development and Preliminary Validity Evidence for the Direct Behavior Rating-Classroom Management (DBR-CM). Issue 2 (3rd April 2021) - Sims, Wesley A.; King, Kathleen R.; Reinke, Wendy M.; Herman, Keith; Riley-Tillman, T. Chris
ABSTRACT: Effective classroom management is of critical importance to the success of universal, Tier I supports and services. Unfortunately, teacher-reported deficits in classroom management training are well documented. In response, use of professional development activities such as consultation, coaching, and on-going performance feedback emphasizing skill-building have proliferated. The Direct Behavior Rating-Classroom Management (DBR-CM) was developed to facilitate screening and formative data collection to drive these activities. This study presents the background, development, and preliminary psychometric evidence for the DBR-CM. Specifically, this study examined inter-rater reliability and concurrent validity in support of the DBR-CM. Findings are promising with inter-rater reliability approaching or exceeding acceptable agreement levels and significant correlations noted between DBR-CM scores and concurrently completed measures of teacher classroom management behavior and perceived self-efficacy. Implications for use and future research are discussed, including further validation and refinement of the DBR-CM and its use within indirect, consultative service delivery.